The science behind TCM and Gut microbiota interaction—their combinatorial approach holds promising therapeutic applications - Xia, Wenrui; Liu, Bei; Tang, Shiyun; Yasir, Muhammad; Khan, Imran (Frontiers in Cellular and Infection Microbiology, 2022)
The trends toward herbal medicine as an alternative source for disease treatment is increasing worldwide. However, little information is available about post-pharmacological oral therapeutics of the orally intake medicines that are exposed to trillions of microbes, known as gut microbiota (GM). The therapeutic paradigm of the Traditional Chinese medicine (TCM) has already entered an exciting new horizon where the potential of GM is harnessed for the better understanding and improved efficacy of the TCM. This interaction between TCM and GM is harnessing the wholistic approach and making landmark achievements in the field of disease diagnosis, prognosis, and treatment. The effectiveness of TCM is a multi-pathway modulation, and so is the GM. This review provides an insight into the understanding of a holistic view of TCM and GM interaction. Furthermore, this review is briefly describing the mechanism that how could TCM-GM combinedly confront various sicknesses. This review also discusses the dilemma whether TCM is either acting as a substrate for a group of bacterial species and kill others or improve host physiology that alternatively effect GM diversity and composition.